A Novel Wavelet-based Optimal Linear Quadratic Tracker for Time-varying Systems with Multiple Delays - Malmir, Iman (Statistics, Optimization & Information Computing, 2021)
A novel method for solving optimal tracking control of linear quadratic time-varying systems with different forms of time delays in state and input variables and with constraints is presented in this paper. Using the concepts of two powerful wavelets, Legendre and Chebyshev wavelets, we convert the optimal tracking problem to a static optimization one. The method is presented in a general from by which one can utilize it by other wavelets. The proposed method has the ability to solve the problems with systems of integer and fractional orders. After determining open-loop solutions of time-delay tracking systems, closed-loop suboptimal controller is designed. A highly successful wavelet-based suboptimal controller is introduced in this work. This alternative method is applied on some optimal tracking systems.